Open-bite treatment of a case by means of zygomatic plate anchorage - Motro, Melih; Çakırer, Banu (Marmara Dental Journal, 2013)
Treatment of anterior open bite cases is usually a challenging issue and the treatment results are often hard to maintain. Many treatment modalities were presented throughout the years in the literature where in most, malocclusion is corrected primarily by extrusion of the incisors or preventing passive eruption of posterior teeth. Surgical correction is another main approach in treatment of skeletal openbite cases. However, patients may hesitate to have surgery due to the risks, complexity and costs of this treatment. In this case report a minimally invasive method is shown in which posterior teeth are intruded by using zygomatic anchorage. For this purpose multi purpose implants were placed on the zygomatic buttress area to act as anchorage units. The intrusive force application was started by attaching two 9mm NiTi coil springs bilaterally to the bended “I” shaped processes that access to the oral cavity through the mucosa. Posterior dentoalveolar intrusion was achieved in 6 months and the intrusion was maintained with wire ligation between the implant and the molar tubes throughout the treatment. Lower face height to total face height ratio decreased by 1%. 1mm overbite was achieved. Normal smile line concomitant with the lower lip contour and esthetic gingival exposure was also achieved. If intrusion of the posterior teeth is necessary skeletal anchorage through zygomatic multipurpose implants can be used as a good treatment alternative to orthognathic surgery.
Keywords: Zygomatic Anchorage, Open-bite, Molar Intrusion